Moderating Effect of Psychological Distress on the Link between Social Media Adoption and Learning Outcomes - Georgia Moschogianni (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The study examine that e-learning readiness has impact on academic performance and learning engagement, moderating role of psychological distress and mediating role of social media adoption, drawing with social cognitive theory among university students in Athese, Greece. Methodology: A questionnaire was employed and data collected 378 graduate students through quantitative field survey research design among university students. Findings: The e-learning readiness has a significant impact on academic performance and learning engagement. Also, significant mediating role of social media adoption between e-learning readiness with academic performance and learning engagement. Furthermore, significant moderating role of psychological distress between social media adoption with academic performance and learning engagement. In addition, students used online learning tools in their studies. Implications/Novel Contribution: This study contributes to theoretical and policy implications based on RBV theory by demonstrating how human resources practices are dynamic and may be sustained for a competitive advantage. Moreover, the study has practical implications for leaders of higher education that they can see how technology and talent management should complement each other’s contributions to facilitate performance sustainability. Online learning environments and e-learning environments specifically differ from general classroom environments in that they are, generally, self-paced learning environments where learners study at flexible times. The moderating role of psychological distress is a particularly important finding, as this finding is indicative that even academically high-performing, engaged, and prepared students would struggle to perform if their mental health needs were not fulfilled. Therefore, illustrating pathways for educators and educational stakeholders to strengthen or build better support systems for students and resilience for both students and educators.